Pemilihan Umum, Demokrasi dan Paradigma Baru Kehidupan Politik: Beberapa Catatan - Satya Arinanto (Unisia, 1999)
General Election has been the most important partof the whole processes to be a democratic state. Some significant changes have occured In the General Election system held in 1999 including the comitte, contestants and rules of the game. The new paradigm of the General Election has been the hope, on one hand, and the anxiety, on the other hand, to raise a democratic climate. The writer has offered some optimistic ideas that the General Election of 1999 will be more democratic.